2019
DOI: 10.1096/fj.201802307r
|View full text |Cite
|
Sign up to set email alerts
|

iPSC‐ and mesenchymoangioblast‐derived mesenchymal stem cells provide greater protection against experimental chronic allergic airways disease compared with a clinically used corticosteroid

Abstract: The airway remodeling (AWR) associated with chronic allergic airways disease (AAD)/asthma contributes to irreversible airway obstruction. This study compared and combined the antiremodeling and other effects of induced pluripotent stem cell and mesenchymoangioblast‐derived mesenchymal stem cells (MCA‐MSCs) with the corticosteroid dexamethasone (Dex) in experimental chronic AAD/asthma. Female BALB/c mice subjected to 11 wk of ovalbumin (Ova)‐induced chronic AAD were intranasally administered MCA‐MSCs (1 × 106 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Although initially tested in aGVHD, iPSC-derived MSCs may be used in the future for a range of other clinical targets. Encouraging data on the potential utility of iPSC-derived MSCs manufactured using this platform have already been generated in preclinical models of critical limb ischemia 33 , asthma 34,35 , organ transplant rejection 36 and acute respiratory distress syndrome 37 . Furthermore, we note that primary MSCs have been investigated for a wide range of other therapeutic indications, and we hypothesize that iPSC-derived n, number of patients; first response, improvement by at least one aGvHD grade; best response, maximal improvement in aGvHD grade.…”
Section: Discussionmentioning
confidence: 99%
“…Although initially tested in aGVHD, iPSC-derived MSCs may be used in the future for a range of other clinical targets. Encouraging data on the potential utility of iPSC-derived MSCs manufactured using this platform have already been generated in preclinical models of critical limb ischemia 33 , asthma 34,35 , organ transplant rejection 36 and acute respiratory distress syndrome 37 . Furthermore, we note that primary MSCs have been investigated for a wide range of other therapeutic indications, and we hypothesize that iPSC-derived n, number of patients; first response, improvement by at least one aGvHD grade; best response, maximal improvement in aGvHD grade.…”
Section: Discussionmentioning
confidence: 99%
“…And the effect of LTRA on attenuate airway remodeling by inhibiting TGF-β/Smad signaling has been also demonstrated [ 36 ]. However, recent studies have also focused on the ineffective of glucocorticoid in treating airway remodeling [ 37 , 38 ]. Our results showed that neither glucocorticoid or montelukast sodium can reverse the changes of EMT markers induced by TGF-β1/IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…However, this notion is counterbalanced by the fact that human MSC and NSC can reach the brain after intranasal administration in immunocompetent rodent models of brain disorders [ 12 , 51 ]. Moreover, intranasally administered human MSC derived from clinical-grade human iPSC line were shown to provide greater protection than corticosteroids against allergic airways disease in mice [52] . Intranasally applied NSC have also been successfully delivered to the brain in a model with strong local, i.e.…”
Section: Discussionmentioning
confidence: 99%